All Days 2012
DOI: 10.2118/160839-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Optimized Casing Exit and Solid Expandable Technologies: Bringing New Life to Dead Wells

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSix recent well recompletions in Hassi Messaoud Field, Algeria utilized shallow angle casing exit technology in conjunction with solid expandable liner systems to optimize a workover campaign and revitalize an aging field. The operator in this field faced recompletion challenges such as existing well size constraints, reducing top-down drilling cost, and maximizing completion clearance while creating maximum reservoir contact (MRC) wells. The combination of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…Research and applications on expandable casing have been reported by various references [2,3,4,5,6,7,8,9]. Reference [10] presented their work on evaluating the sealing integrity of an expandable casing section, with specific focus on the sealing ring.…”
Section: Introductionmentioning
confidence: 99%
“…Research and applications on expandable casing have been reported by various references [2,3,4,5,6,7,8,9]. Reference [10] presented their work on evaluating the sealing integrity of an expandable casing section, with specific focus on the sealing ring.…”
Section: Introductionmentioning
confidence: 99%